Pernikahan Usia Dini Menurut Interpretasi Ayat Al-Qur’an - Matondang, Husnel Anwar; Suib, Muhammad; Ahbaroni, Muhammad Dipa; Irwana, Arini Suci; Siregar, Muhajiroh Alya (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Early marriage is a common problem in every family. Given that the child is the successor and hope in the future. In fact, early marriage is increasingly happening, this is evidenced by the movement of Aisah Wedding's. There are several factors that cause many early marriages, among others; First, religious understanding that is not oriented to the best interests of the child. Second, cultural factors and traditions of the community that should not reject the application. Third, lifestyle. Fourth, poverty. Fifth, legal controversy. With the demikia of early marriage is not a solution to the problem that is happening, it is necessary to prepare the maturity of the child both theologically, physically and mentally. Keywords : interpretation of verse, early marriage.